Keefektifan Model Pembelajaran Project Based Learning untuk Meningkatkan Kecerdasan Visual-Spasial dan Kreativitas Anak Usia 5-6 Tahun - Hakim, Ardiana Nur Maulida; Sagala, Anita Chandra Dewi; Muhtarom, Muhtarom (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2025)
Teaching and learning activities are carried out through teacher guidance. The results of observations made that in the learning process the teacher has applied various teaching variations in order to achieve learning objectives. In carrying out a learning process, teaching variations are applied evenly. However, there are some whose implementation in the learning process is still not optimal so that there needs to be mastery or improvement in its implementation. In other cases, there are still some teachers who focus too much on learning to read, write and count, so that children's intelligence and creativity are not optimally honed. The research method used in this study is the experimental research method. The research design used is a pre-experimental research design. The results of data processing obtained during the study showed an increase in children's visual spatial abilities and creativity. In the data normality test, it is stated that it is normally distributed if the significance value is 0.05. The results of the data normality test from the variables of visual spatial ability and creativity show that the data is normally distributed with a Sig. value. Visual spatial ability 0.200 0.05, and a Sig. value. creativity 0.076 0.05. In the homogeneity test, the data is stated to be homogeneous if the significance value is 0.05. The homogeneity test of the variables of children's visual spatial ability and creativity also shows that the data is homogeneous, with a Sig. value of visual spatial ability of 0.556 0.05 and a Sig. value of children's creativity of 0.625 0.05.